1461Neighbourhood disadvantage and early childhood mental health inequities across a population of children at school-entry. (2nd September 2021) - Alderton, Amanda; O'Connor, Meredith; Villanueva, Karen; Gunn, Lucy; Turrell, Gavin; Boulange, Claire; Badland, Hannah
Abstract: Background: Mental health inequities are shaped by the environments where children develop, including neighbourhoods. Children living in disadvantaged neighbourhoods tend to have poorer development outcomes, yet little evidence has examined positive mental health outcomes, like competence, in young children. Methods: We examined associations between neighbourhood disadvantage and young children's competence, as well as mental health difficulties (internalising and externalising), holding constant demographic characteristics and maternal education using multilevel logistic regression (Markov Chain Monte Carlo estimation). Data were from the 2018 Australian Early Development Census, including over 250, 000 children entering their first year of school (age approximately 5 years). Results: Children living in Australia's most disadvantaged neighbourhoods had higher odds of externalising difficulties (AOR: 1.34; 95% credible interval 1.29 to 1.38), internalising difficulties (AOR: 1.29; 95% credible interval 1.24 to 1.33), and lower odds of competence (AOR: 0.72; 95% credible interval 0.69 to 0.74) than children in the least disadvantaged neighbourhoods. Conclusions: Across both mental health difficulties and competence, neighbourhood-level inequities were evident. Future research should identify specific neighbourhood features that could address these inequities. Availability of population linked geospatial and child development data in Australia offers opportunities to address these gaps and is prioritised as the next step in this research program. Key messages: Children in disadvantaged neighbourhoods face lower likelihood of positive mental health (competence) and higher likelihood of mental health difficulties. Identifying specific neighbourhood features that could address these inequities is a priority.